Pedigree-Based Deciphering of Genome-Wide Conserved Patterns in an Elite Potato Parental Line - Li, Xiaochuan; Xu, Jianfei; Duan, Shaoguang; Bian, Chunsong; Hu, Jun; Shen, Huolin; Li, Guangcun; Jin, Liping (Frontiers in Plant Science, 2018)
Elite parental lines are more likely to breed fine varieties, but knowledge about elite parents and their genetic backgrounds is limited. In this paper, we investigated the pedigree relationships of potato varieties bred worldwide and in China. Several elite parents were identified, and these parents were more frequently used as parents in breeding programs across different time periods and countries. We next used 2b-RAD, a reduced-representation sequencing method, to genotype the elite parent Mira and 24 of its offspring. These cultivars span 5 generations, making this lineage the longest continuous pedigree among Chinese bred potatoes. A total of 47,314 tetraploid SNPs identified by FreeBayes were used to trace the conserved segments of the Mira genome. The conserved segments had identical or similar allele-specific SNPs across the analyzed genotypes. In Mira, 3,788 segments comprising over 10,000 bp, or 20.8% of the genome, were defined as conserved segments. These segments contain genes involved in crucial biological processes that are of special interest to breeders. These regions, which have been conserved across generations of highly selective breeding, may be helpful for further breeding and performing genome-wide breeding by design.